Soil conservation practices in maize-bean production systems in Cuba. - Alfonso, Claro A. (2006)
Two trials were conducted in production conditions in watersheds of the Pinar del Río province, one in Campo Hermoso and the other in La Comunidad La Leña, Cuba. At both sites, rotations were conducted involving two bean varieties: BAT 304 and Tomeguin 93, followed by maize associated with Mucuna deeringianum. Border ridges were established with Stizolobium d. and Canaraline protected by live barriers of Leucaena leucocephela and Gliricidia sepium. Soil losses were estimated in sedimentation boxes and Valday limnigraphs in Campo Hermoso, but in La Leña only differences in slope and maximum depth of sediments at the end of each crop cycle were determined. The soil is a Quartzic Ferralytic (Ultisol), and fertilization was carried out according to nutrient reserves. Field preparations were done with animal traction. Results at the end of five years showed a reduction in soil losseseven below the acceptable threshold (5 t/ha), an increase in height of terraces due to accumulated sediments; greater water availability in the sedimentation area; greater ground cover in the rainy season; and reduced erosive effect by rain. Results also show recycling of nutrientsthrough green manure, and increased yields compared to plots with no conservation practices. In conclusion, integrated management of several factors on hillsides with more than 5% slope is necessary for conservation of soil and waterresources.